Understanding Teaching Excellence in Higher Education: Towards a Critical Approach - Skelton, Alan (Key Issues in Higher Education, 2005)
What makes a university teacher 'excellent'? As debates rage about whether this is down to subject knowledge, communication skills, taking a research-led approach or being a technological whiz, this book provides the first in-depth examination of teaching excellence in higher education. Identifying and examining interpretations of teaching excellence, it considers what ‘excellent’ means and implies for practice. Part 1: Beginnings 1. Introduction 2. A Critical Framework Part 2: Familiar Faces 3. Awards for Teachers 4. Institutions and Teaching Excellence 5. The Contribution of Subject Disciplines Part 3: Alternative Explorations 6. Local Knowledge: 'Ordinary' Teacher and Student Perceptions 7. Internationalisation and Inter-Cultural Learning 8. Seduced by Glitz and Glamour: Press Reporting of Teaching 9. Excellence 10. Professional Development and Teaching Excellence Part 4: Future Horizons 11. Lost in the Translation? 12. Research into Teaching Excellence in Higher Education 'Skelton writes with an engaging critical zeal, and his book will certainly help many talented, competent, and hardworking teachers in higher education in UK to understand why, and how, a few members of their profession become mysteriously singled out for recognition and reward as “excellent”, whilst they themselves do not.' 'Here we have a bold and original book that cruelly exposes some of the myth-making mechanisms that politicians and their handservants have clumsily sought to impose upon contemporary HE. Extremely well written and a model of clear organisation.' - British Journal of Educational Technology Vol 38 No 1 2007